Corrole-phenothiazine and porphyrin-phenothiazine dyads connected at β-position: Synthesis and photophysical properties. (August 2017) - Kandhadi, Jaipal; Cheng, Fan; Wang, Hua-Hua; Ali, Atif; Wang, Li-Li; Wang, Hui; Liu, Hai-Yang
Abstract: Two novel donor-acceptor dyads, in which phenothiazine (PTZ) connected at β-pyrrolic position of either freebase corrole (TPC) or freebase porphyrin (TPP) via vinylic spacer have been synthesized. Both the dyads were characterized by ESI-MS, IR, 1 H NMR (1D and 2D 1 H- 1 H COSY and J-Resolved), UV–Vis, Study state Fluorescence, Time-resolved fluorescence (Time-correlated single photon counting (TCSPC), Streak Camera) as well as electrochemical methods. In the absorption spectra of the dyads, both Soret and Q-bands were red shifted by 8–20 nm indicating weak electronic communication between the two chromophores. However, the fluorescence emission from the PTZ of the dyad was efficiently quenched (96–99%) as compared to pristine PTZ where the dyad was excited at 310 nm, which is attributed to singlet-singlet excited energy transfer. Fluorescence emission from porphyrin part of the TPP-PTZ dyad also quenched when excite the dyad at 420 nm, which is ascribed to photoinduced electron transfer from ground state of PTZ to excited state of porphyrin. In contrast, when excite the corrole at 420 nm in TPC-PTZ dyad, we found there are no significant changes in photophysical properties. In both the cases the solvent dependence of the rate of energy and electron transfer was observed. Graphical abstract: Highlights: Two novel dyads in which PTZ connected at β-pyrrolic position of either free base porphyrin/corrole with vinylic spacer. Photoinduced singlet-singlet energy transfer from PTZ to corrole/porphyrin was observed (λex  = 310 nm). The energy transfer is more efficient in TPP-PTZ (99%) than the TPC-PTZ (96–98%) when excitation of the dyad at 310 nm. Quenched emission of porphyrin in TPP-PTZ dyad was observed due to photoinduced electron transfer (λex  = 420 nm). Solvent dependent rates of the energy and electron transfer was discussed.